Evaluation of flavonoids from Zostera asiatica as antioxidants and nitric oxide inhibitors - Kim, Hojun; Jeong, Huijeong; Hong, Joo Wan; Ju, Eunshin; Kong, Chang-Suk; Seo, Youngwan (Biotechnology and bioprocess engineering, 2016)
Zostera asiatica is one of the five members of the genus Zostera that can be found in Korea. Studies have reported the phytochemical properties and bioactivities of Zostera species. Current study focused on the antioxidant effects of Z. asiatica as a part of ongoing research for bioactive substances from marine resources. Results indicated that a crude extract of Z. asiatica not only scavenged on peroxynitrite in vitro and on intracellular reactive oxygen species (ROS) but also inhibited production of nitric oxide (NO). The crude extract was subjected to solvent fractionation for bioactivity-based separation using aforementioned three bioassay systems. From the active n-butanol fraction, two flavonoids were isolated and characterized as luteolin ( 1 ) and luteolin-3’-sulfate ( 2 ). Both flavonoids showed significant antioxidant effects. In conclusion, Z. asiatica was demonstrated to possess antioxidant effect partly attributed to isolated flavonoids, the first such effect reported from Z. asiatica , to the best of our knowledge.